Pelatihan Building My Own Personality untuk Meningkatkan Organizational Citizensip Behavior - Aninta Alijona (Universitas Muhammadiyah Jember, 2021)
This training aims to examine the effect of Building My Own Personality training to Organizational Citizenship Behavior on student Executive Board and the administrators at the Faculty of Business and Economics, University of Surabaya. This research was conducted in the form of quasi-experimental design with one group pretest-posttest. Participants in this study were members and administrators of BEM Faculty of Business and Economics, University of Surabaya, amounting to 25 people. In this study measurements were taken on Organizational Citizenship Behavior aspects to see the effect of the implementation of the training program. The results showed that the scotch produced was 10.485 (T table 2.064) with a significance (2 tailed) of 0,000. This means that there are significant differences in participants' OCB scores before and after training. Future research with related topics is still very much needed to see the effect of this training with various participants and other methods.